Determinants of the tourism activity of school pupils (aged 15-19) from Słupsk and Częstochowa - Parzych, Krzysztof (Turyzm/Tourism, 2010)
The purpose of this article is to describe the different types of tourism undertaken by school pupils (aged 15–19) through the example of their tourism trips. Two cities were used: Słupsk and Częstochowa. Analyses of the differing forms of tourism have been made in the context of geographical, socio-economic and demographic determinants for both cities.